1997
DOI: 10.1002/(sici)1099-1395(199706)10:6<420::aid-poc898>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Aldehydes With Permanganate in Acidic and Alkaline Media

Abstract: The oxidation mechanism of aldehydes with permanganate was studied in acidic and alkaline media on acetaldehyde, propionaldehyde, pivalaldehyde (2,2Ј-dimethylpropanal) and chloral substrates. On addition of water to acetaldehyde dissolved in organic solvents the rate increased, and therefore it may be stated that the hydrate form is more reactive than the aldehyde form. Acid-catalysed nucleophilic addition of permanganate is suggested. In alkaline medium a mechanism based on electron abstraction from the alkox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Permanganate can be present as a pure solid (Shaabani et al, 2005) or supported in polymeric materials (Chacko and Mathew, 2003). Jaky and Szammer (1997) showed that the addition of water to the organic solvents increased the reaction rates, indicating that the hydrate form of aldehydes is more reactive than the free form, and that acid catalyzed nucleophilic addition of permanganate is involved. Although not directly applicable to our study, this literature suggests that heterogeneous VOC-permanganate chemistry involves complex mechanisms, in which the presence of moisture likely plays a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…Permanganate can be present as a pure solid (Shaabani et al, 2005) or supported in polymeric materials (Chacko and Mathew, 2003). Jaky and Szammer (1997) showed that the addition of water to the organic solvents increased the reaction rates, indicating that the hydrate form of aldehydes is more reactive than the free form, and that acid catalyzed nucleophilic addition of permanganate is involved. Although not directly applicable to our study, this literature suggests that heterogeneous VOC-permanganate chemistry involves complex mechanisms, in which the presence of moisture likely plays a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…However, the absorbance of the reaction mixture decreased with time. This revealed the formation of an intermediate pre-equilibrium complex which led to product formation [4]. Applying steady state approximation:…”
Section: Spectral Studiesmentioning
confidence: 99%
“…Potassium permanganate discovered by Margueritte in 1846 has now been widely used for redox reactions involving a variety of chemical reactions. It is a versatile strong oxidizing agent in both acidic and alkaline media which has been employed for the oxidation of various organic compounds like alcohols [1][2][3], aldehydes and ketones [4][5][6], amines [7], glyoxal and glyoxalic acid [8]. There are few reports in the literature on the oxidation of Diols.…”
Section: Introductionmentioning
confidence: 99%
“…However, the absorbance of the reaction mixture decreased with time. This revealed the formation of an intermediate preequilibrium complex which led to product formation [4].…”
Section: Spectral Studiesmentioning
confidence: 99%
“…Potassium permanganate discovered by Margueritte in 1846 has now been widely used for redox reactions involving a variety of chemical reactions. It is a versatile strong oxidizing agent in both acidic and alkaline media which has been employed for the oxidation of various organic compounds like alcohols [1][2][3], aldehydes and ketones [4][5][6], amines [7], glyoxal and glyoxalic acid [8].…”
Section: Introductionmentioning
confidence: 99%